The Role of Land Deed Making Officials (PPAT) in the Application of Land and Building Rights Acquisition Fees (BPHTB) in Relation to Land Sale and Purchase Deeds - Febrian, Rayhadi Candra (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2022)
The implementation of tax revenue from BPHTB is submitted to the Notary's office, in its position as PPAT it also plays a role in increasing tax revenue from BPHTB related to the deed. Formulation of the problem, what is the role of the PPAT in collecting Land Title Acquisition Fees (BPHTB) related to the deed he made and what obstacles occurred in collecting Land Rights Acquisition Fees (BPHTB) as well as examples of Land Sale and Purchase Deeds. This research used the empirical juridical research methods, to analyze qualitatively, specifications for writing descriptive analysis, sources and types of data using primary and secondary data, data collection techniques by collecting primary and secondary data, qualitative descriptive data analysis techniques, after the data is collected it is poured in the form of logical descriptions and systematically then analyzed, conclusions drawn deductively. The results of research on the role of the PPAT in the application of Land Acquisition Fees (BPHTB) relating to the deed of sale and purchase of land it makes, it is hoped that PPAT will play an active role in requiring BPHTB payments in transferring land and building rights related to the deed it made. Obstacles that arise in the collection of Land Rights Acquisition Fees (BPHTB) as PPAT are related to the deed he made: a) lack of information and socialization regarding BPHTB regulations that are constantly evolving; b) NJOP data for the last year has not been issued if the sale and purchase is made at the beginning of the year; c) Sale and purchase underhanded or distribution of inheritance that has not been subject to BPHTB for land that has not been certified cannot be subject to legal sanctions.Keywords: Acquisition; Land; Officer.